Economic Inequality and the Size of Government Expenditure Shocks: An Empirical Exercise - Veršič, Sabina (Naše gospodarstvo/Our economy, 2024)
Empirical literature explains the heterogeneity of fiscal multiplier estimates through the analysis of various cyclical and structural determinants of economies, with economic inequality, as one of the key structural characteristics, receiving relatively little attention so far. In this study, using a wide sample of countries and applying the vector autoregression methodology, we first estimated fiscal multipliers and the impact of fiscal stimuli on the dynamics of the price level. The findings indicate that the estimated fiscal multipliers are mostly positive, and fiscal stimuli tend to produce an inflationary effect. Subsequently, we examined the variability in the size of fiscal multipliers in relation to various indicators of income and wealth inequality. The key findings of this study reveal that as economic inequality increases, particularly in the context of income disparities, the size of fiscal multipliers also rises. This insight is particularly important for policymakers in designing appropriate fiscal measures in an evolving macroeconomic environment.